2015
DOI: 10.1007/s12088-015-0511-2
|View full text |Cite
|
Sign up to set email alerts
|

Using a Label Free Quantitative Proteomics Approach to Identify Changes in Protein Abundance in Multidrug-Resistant Mycobacterium tuberculosis

Abstract: Reports in recent years indicate that the increasing emergence of resistance to drugs be using to TB treatment. The resistance to them severely affects to options for effective treatment. The emergence of multidrug-resistant tuberculosis has increased interest in understanding the mechanism of drug resistance in M. tuberculosis and the development of new therapeutics, diagnostics and vaccines. In this study, a label-free quantitative proteomics approach has been used to analyze proteome of multidrug-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…This protein is an oxidoreductase that is necessary for the growth of mycobacteria and has a potential role in detoxification of toxic metabolites. Previous studies have shown that this enzyme was differentially represented between INHr and INHs strains [23,24] and for STR [25]. In the present study, higher transcript levels of Rv2971 in the 2093, compared to other strains, were detected.…”
Section: Non-specific Bacterial Response To Anti-tuberculosis Therapysupporting
confidence: 64%
“…This protein is an oxidoreductase that is necessary for the growth of mycobacteria and has a potential role in detoxification of toxic metabolites. Previous studies have shown that this enzyme was differentially represented between INHr and INHs strains [23,24] and for STR [25]. In the present study, higher transcript levels of Rv2971 in the 2093, compared to other strains, were detected.…”
Section: Non-specific Bacterial Response To Anti-tuberculosis Therapysupporting
confidence: 64%
“…The inactivation of their respective orthologues in M. smegmatis has suggested that they are involved in the biosynthesis of cell wall components and arabinogalactan, working as a potential flippase candidate that exports the lipid intermediate containing the galactan structure prior to its arabinosylation [97]. RfbE was identified as one of the most expressed proteins in the proteomic analysis of a one-year-old dormant M. tuberculosis [98] bacillus and is highly abundant in multidrug-resistant and susceptible M. tuberculosis isolates [99]. RfbDE seems to be essential for in vitro growth [40,46] and is required for growth in C57BL/6J mouse spleen [34].…”
Section: Transporters Involved In the Recycling And Transport Of Memb...mentioning
confidence: 99%
“…The supernatant containing the whole cell lysate proteins was retained and determined the concentrations with BCA according to the manufacturer’s instructions. The lysate was sterilized through a filter membrane with the pore diameter of 0.22 μm (Pall Corporation, Ann Arbour, MI, USA) and stored at −80 °C until further analysis [ 76 ]. The lysate proteins were identified by 12% SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%